Implications of Parents for Continuing Children's Education in Katilombu Village, Sampolawa District, South Buton Regency - La Ode Yuda Febriadi; Madi Madi (AIQU: Journal Multidiscipliner of Science, 2023)
The objectives of this research are: (1) To find out what parents' implications are for children's education in Katilombu Village, Sampolawa District, South Buton Regency; (2) To determine the progress of children's continuing education in Katilombu Village, Sampolawa District, South Buton Regency. The research approach used in this research is qualitative research. The data collection techniques used were through observation, interviews and documentation. The data collection procedure involves conducting research directly at the location used as the research target and also collecting data by quoting expert opinions, then when the data is collected the author carries out a qualitative descriptive analysis. Every research activity certainly has a population and sample. The population for this study was 163 people, while the sample was 18 people. The results of the research show that: (1) the implications of parents or the role of parents in Katilombu Village, Sampolawa District, South Buton Regency are generally very good, they guide their children well and motivate their children to remain enthusiastic in pursuing and achieving goals. education up to a higher level. (2) basically the continuation of children's education in Katilombu Village is said to be very good because parents in Katilombu Village always instill motivation in their children to be enthusiastic about achieving education up to higher education.